Separating the influence of electric charges in magnetic force microscopy images of inhomogeneous metal samples - Arenas, Mónica P.; Lanzoni, Evandro M. [UNESP]; Pacheco, Clara J.; Costa, Carlos A.R.; Eckstein, Carlos B.; de Almeida, Luiz H.; Rebello, João M.A.; Deneke, Christoph F.; Pereira, Gabriela R. (Elsevier, 2018)
In this study, we investigate artifacts arising from electric charges present in magnetic force microscopy images. Therefore, we use two austenitic steel samples with different microstructural conditions. Furthermore, we examine the influence of the surface preparation, like etching, in magnetic force images. Using Kelvin probe force microscopy we can quantify the charges present on the surface. Our results show that electrical charges give rise to a signature in the magnetic force microscopy, which is indistinguishable from a magnetic signal. Our results on two differently aged steel samples demonstrate that the magnetic force microscopy images need to be interpreted with care and must be corrected due to the influence of electrical charges present. We discuss three approaches, how to identify these artifacts – parallel acquisition of magnetic force and electric force images on the same position, sample surface preparation to decrease the presence of charges and inversion of the magnetic polarization in two succeeding measurement.
Keywords: Aging; Austenitic stainless steels; Carbides; Kelvin probe force microscopy; Magnetic force microscopy; Magnetic properties